أثر سياسة تمهيد الدخل على القيمة الاقتصادية المضافة لمجموعة من المؤسسات الجزائرية-دراسة قياسية باستخدام نماذج بانل الديناميكي للفترة (2012-2019)- - حتحوت, مريم; بورديمة, سعيدة (جامعة الوادي - University of Eloued, 2022)
The study aims to determine the impact of the political income smoothing on economic value added of a group of Algerian companies for the period 2012- 2019, as well as determing the nature of the relationship between the two variables, using the dynamic panal modeling method and relying on generalized method of moments in estimation. The results of the study found to negative impact between the income smoothing and economic value added that as a misleading policy for the actual performance of the company.
The Impact of the Income Smoothing policy on the Added Economic Value of a group of Algerian companies-An Econometric Study using Dynamic Panel Models during the period (2012-2019)
مقال
Keywords: سياسة تمهيد الدخل ; القيمة الاقتصادية المضافة ; نموذج ايكال ; طريقة العزوم المعممة.